2021
DOI: 10.1002/1348-9585.12208
|View full text |Cite
|
Sign up to set email alerts
|

Differences between fixed day shift nurses and rotating and irregular shift nurses in work-related musculoskeletal disorders: A literature review and meta-analysis

Abstract: Objectives Work‐related musculoskeletal disorders (WMSDs) are common occupational injuries for nurses. Furthermore, rotating and irregular shift work may exacerbate muscle tension and pain in nurses. The objective of this study was to examine the differences between fixed day shift (FDS) nurses and rotating and irregular shift (RS + IS) nurses in WMSDs using a systematic literature review and meta‐analysis. Methods Databases including PubMed, CINAHL, Cochrane Library, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
(42 reference statements)
0
16
0
Order By: Relevance
“…Dental traumatic injuries are mainly caused by tra c accidents, violence, and intense sports activities [8, [12][13]; however, there have been no studies on dental injuries caused by accidents in the workplace. Traumatic dental injuries that can occur in the work environment can drastically impact oral health and quality of life [14]. However, only few studies have investigated exposure to acidic substances in the work environment [15] and occupational dental erosion [16].…”
Section: Introductionmentioning
confidence: 99%
“…Dental traumatic injuries are mainly caused by tra c accidents, violence, and intense sports activities [8, [12][13]; however, there have been no studies on dental injuries caused by accidents in the workplace. Traumatic dental injuries that can occur in the work environment can drastically impact oral health and quality of life [14]. However, only few studies have investigated exposure to acidic substances in the work environment [15] and occupational dental erosion [16].…”
Section: Introductionmentioning
confidence: 99%
“…This clearly established work hours as an independent risk factor for MSD in nursing populations. Overall, the link between work hours and MSD is most robust for back pain, while data regarding neck and shoulder pain are less clear (Caruso/Waters 2008;Chang/Peng 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Other work hours-related exposures that remain poorly understood include quick returns, weekend work, overtime, and on-call or split schedules. And while a recent meta-analysis by Chang/Peng (2021) based on 17 studies and >18,000 individuals reported a 40% MSD risk increase for "irregular and shift working" nurses as compared to "day shift" nurses, recommendations for work schedule design remain inconclusive, due to their very basic definition of shift work: "Any fixed shift beginning between 7:00 and 9:00 in the morning was defined as FDS [fixed day shift]. All remaining shifts were defined as RS + IS [rotating shift + irregular shift]" (Chang/Peng 2021, p. 2).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other agencies or institutions, nurses in hospitals must serve until the patient is discharged or treated as an outpatient. Nurses in hospitals must be managed according to work shifts to serve patients within 24 hours (Chang & Peng, 2021).…”
Section: Introductionmentioning
confidence: 99%